(untitled) (African Journal of Law and Politics, 2023)
The expulsion of foreigners is a reality in Central Africa. This practice, which is governed by the national legislation of each State, arouses curiosity when analysing its motivations, which are diverse. In addition to serving legitimate causes, including the prevention and preservation of public order, public security, public health, public morality, illegal immigration and the exercise of a dangerous activity within those States, they are also an opportunity for other States to keep foreigners away from their borders and from the sharing of their wealth. The expulsion of foreigners within these States would therefore be a disguised means of limiting demographic invasion, economic spoliation and safeguarding their sovereignty. In all cases, it should be remembered that expulsion is an exclusive prerogative of each State, whose assessment of necessity is devolved to its administrative police authorities by virtue of its sovereignty.